Judgmental Biases and Consumer Behaviour in Smartphone Selection - Hlekau, Valiantsin (2023)
The master thesis is focused on the issue of contemporary judgmental biases found and observed among the consumers while selecting a smartphone. The smartphone was chosen as a subject of research due to the fact that it’s a multifunctional device, which has relatively recently become an integral part of our lives by being used in work, leisure and other aspects of life. The master thesis consists of two major parts — a theoretical part and a practical part. In the scope of the paper’s theoretical part, such issues, as judgmental biases, their relation to the consumers’ behaviour and their preferences during purchase decisions are discussed. In practical part, the experiment is set to determine the presence of biases during the process of customer choice. In the process of the data processing the main existing judgmental biases are determined and the main consequences of the fact of existence of such biases for final customers and smartphones’ producers are set.